Comparison of logistic regression and random forest algorithms for airports runway assignment - I Kanjanasurat; W Jungsuwadee; A Lasakul; C Benjangkaprasert (My University, 2023)
Abstract Various automation systems are currently developed using machine learning techniques. It is used to predict and decide on numerous complex tasks in order to reduce the likelihood of human error. Logistic regression is one of the most widely employed machine learning (ML) algorithm. In this study, the accuracy of logistic regression was compared to that of random forest for the assignment of Suvarnabhumi Airport runways to arriving aircraft. The accuracy of the logistic regression model was determined to be 82%, while the accuracy of the random forest model was 77%. Logistic regression was found to be more precise for predicting the appropriate runway to assign to arriving aircraft.
Keywords: Logistic model tree; Forecasting Techniques and Applications